Comparison of Arterial Spin-labeling Perfusion Images at Different Spatial Normalization Methods Based on Voxel-based Statistical Analysis - Masumoto, Tomoya; Ijichi, Tetsuya; Morimoto, Shoichi; Toyofuku, Tatsuo; Matsushima, Masatoshi; Tani, Kazuki; Kato, Shinichi; Mio, Motohira; Hirata, Takumi (Japanese Journal of Radiological Technology, 2017)
Purpose: Spatial normalization is a significant image pre-processing operation in statistical parametric mapping (SPM) analysis. The purpose of this study was to clarify the optimal method of spatial normalization for improving diagnostic accuracy in SPM analysis of arterial spin-labeling (ASL) perfusion images. Methods: We evaluated the SPM results of five spatial normalization methods obtained by comparing patients with Alzheimer’s disease or normal pressure hydrocephalus complicated with dementia and cognitively healthy subjects. We used the following methods: 3DT1-conventional based on spatial normalization using anatomical images; 3DT1-DARTEL based on spatial normalization with DARTEL using anatomical images; 3DT1-conventional template and 3DT1-DARTEL template, created by averaging cognitively healthy subjects spatially normalized using the above methods; and ASL-DARTEL template created by averaging cognitively healthy subjects spatially normalized with DARTEL using ASL images only. Results: Our results showed that ASL-DARTEL template was small compared with the other two templates. Our SPM results obtained with ASL-DARTEL template method were inaccurate. Also, there were no significant differences between 3DT1-conventional and 3DT1-DARTEL template methods. In contrast, the 3DT1-DARTEL method showed higher detection sensitivity, and precise anatomical location. Conclusions: Our SPM results suggest that we should perform spatial normalization with DARTEL using anatomical images.